Observation of Electrically Tunable van Hove Singularities in Twisted Bilayer Graphene from NanoARPES. Issue 31 (11th June 2020) - Jones, Alfred J. H.; Muzzio, Ryan; Majchrzak, Paulina; Pakdel, Sahar; Curcio, Davide; Volckaert, Klara; Biswas, Deepnarayan; Gobbo, Jacob; Singh, Simranjeet; Robinson, Jeremy T.; Watanabe, Kenji; Taniguchi, Takashi; et al.
Abstract: The possibility of triggering correlated phenomena by placing a singularity of the density of states near the Fermi energy remains an intriguing avenue toward engineering the properties of quantum materials. Twisted bilayer graphene is a key material in this regard because the superlattice produced by the rotated graphene layers introduces a van Hove singularity and flat bands near the Fermi energy that cause the emergence of numerous correlated phases, including superconductivity. Direct demonstration of electrostatic control of the superlattice bands over a wide energy range has, so far, been critically missing. This work examines the effect of electrical doping on the electronic band structure of twisted bilayer graphene using a back‐gated device architecture for angle‐resolved photoemission measurements with a nano‐focused light spot. A twist angle of 12.2° is selected such that the superlattice Brillouin zone is sufficiently large to enable identification of van Hove singularities and flat band segments in momentum space. The doping dependence of these features is extracted over an energy range of 0.4 eV, expanding the combinations of twist angle and doping where they can be placed at the Fermi energy and thereby induce new correlated electronic phases in twisted bilayer graphene. Abstract : An electrostatically gated van der Waals heterostructure composed of twisted bilayer graphene is investigated using nanoscale angle‐resolved photoemission during device operation. The dispersion of the superlattice bands and the energy of the associated van Hove singularities are tuned by varying the charge carrier density in the two twisted graphene layers using the back‐gate voltage.